2019
DOI: 10.5194/hess-23-1533-2019
|View full text |Cite
|
Sign up to set email alerts
|

Future projections of temperature and mixing regime of European temperate lakes

Abstract: The physical response of lakes to climate warming is regionally variable and highly dependent on individual lake characteristics, making generalizations about their development difficult. To qualify the role of individual lake characteristics in their response to regionally homogeneous warming, we simulated temperature, ice cover, and mixing in four intensively studied German lakes of varying morphology and mixing regime with a one-dimensional lake model. We forced the model with an ensemble of 12 climate proj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 65 publications
(85 reference statements)
3
60
0
1
Order By: Relevance
“…environment of lakes, especially their seasonal mix ing regimes 120 (Box 1). In response to climate induced variations in these lake surface conditions, the mix ing regimes of lakes are projected to change through time 11,121,122 , with numerous consequential implications for lake ecosystems.…”
Section: Thermokarst Lakesmentioning
confidence: 99%
See 1 more Smart Citation
“…environment of lakes, especially their seasonal mix ing regimes 120 (Box 1). In response to climate induced variations in these lake surface conditions, the mix ing regimes of lakes are projected to change through time 11,121,122 , with numerous consequential implications for lake ecosystems.…”
Section: Thermokarst Lakesmentioning
confidence: 99%
“…The mixing regimes of marginal lakes have also been described as being very sensitive to changes in water clarity 122,129 . Specifically, a browning of lake surface waters (resulting in a decrease in water transparency), due mainly to terrestrial inputs of dissolved organic matter [130][131][132] , affects the depth at which shortwave radia tion is absor bed within a lake.…”
Section: Dimicticmentioning
confidence: 99%
“…For example, global average warming rates of 0.34 • C per decade have been observed between 1985by O'Reilly et al (2015. Hypolimnetic temperature responds less clearly to warming and has been observed to be warming, cooling or not changing significantly with increasing air temperature (Shimoda et al, 2011;Butcher et al, 2015;Winslow et al, 2017). And, A. I.…”
Section: Introductionmentioning
confidence: 99%
“…Ayala et al: Simulations of future changes in thermal structure of Lake Erken these changing water temperatures have also led to an increased stability and duration of stratification (Butcher et al, 2015;Kraemer et al, 2015). A final consequence of warming lake temperature is projected to be the shift in the mixing regime (Kirillin, 2010;Shimoda et al, 2011;Shatwell et al, 2019;. For example, loss of ice cover in deep lakes is likely to turn amictic lakes into cold monomictic lakes and cold monomictic lakes into dimictic lakes (Nõges et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The latter is not resolved in FLake numerically, but parameterized via few "shape factor"-constants related to the spatial integrals over the stratified layer. Several recent publications, including co-authorship of one of the authors of the present study, (Shatwell et al, 2016;Kirillin et al, 2017;Shatwell et al, 2019;Su et al, 2019) discussed the appropriate choice of the shape factor constants in FLake and have demonstrated that the set of constants used in the NWP-version of the model should be amended if the vertical thermal structure is in question apart from the lake surface temperatures. In particular, the unrealistically weak deep stratification and the corresponding high depth of the surface mixed layer, as reported in the present study, are the results of applying the NWP-constants together with the maximum lake depth as the model lake depth.…”
mentioning
confidence: 94%